Differences of Zinc and Copper Levels In Placenta Blood Normal Neonates and Intrauterine Growth Restriction - Melda Amalia; Yusrawati Yusrawati; Rauza Sukma (Journal of Midwifery, 2018)
Zink and copper are the micronutrients which play a role in the growth and development of fetal and infant. Its deficiency in pregnant women shall give a birth the restriction fetal growth 16,11. This research is proposed to distinguish zinc and copper levels in normal neonates and those restriction fetal growth.The research was conducted with a comparative cross sectional analysis, experienced by three hospitals those are TK III Reksodiwirjo Hospital, Dr. Rasidin Hospital, and Bayangkara Hospital in the city of Padang. It also conducted in the SMAK Padang Chemistry Laboratory in November 2016 - January 2018. The research sample was taken from newborn blood centers for 60 respondents by consecutive sampling. Zinc and copper levels were examined by Atomic Absorption Spectrophotometry (AAS). Hypothesis testing was done by unpaired t testing.The results showed the average zinc level in restriction fetal growth group was 89.34 ± 31.53 µg / dL and normal neonates were 122.703 ± 39.3 µg / dL with p = 0.01. The mean copper content in the restriction fetal growth group was 0.5142 ± 0.15 µg / dL and the normal neonate was 0.6892 ± 0.17 µg / dL with p <0.01The conclusion of this research is zinc and copper levels in normal neonates were significantly higher than neonatal zinc and copper levels restriction fetal growth.